2020
DOI: 10.3390/brainsci10020072
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Astrocytic Kir4.1 Potassium Channels Is Associated with Hippocampal Neuronal Hyperexcitability in Type 2 Diabetic Mice

Abstract: Epilepsy, characterized by recurrent seizures, affects 1% of the general population. Interestingly, 25% of diabetics develop seizures with a yet unknown mechanism. Hyperglycemia downregulates inwardly rectifying potassium channel 4.1 (Kir4.1) in cultured astrocytes. Therefore, the present study aims to determine if downregulation of functional astrocytic Kir4.1 channels occurs in brains of type 2 diabetic mice and could influence hippocampal neuronal hyperexcitability. Using whole-cell patch clamp recording in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 60 publications
1
8
0
1
Order By: Relevance
“…A similar effect was reported in hyperglycaemic cultured astrocytes and in mouse models of diabetes. Hyperglycaemia downregulates K ir4.1 protein in vitro and in vivo, resulting in the increased spontaneous activity of surrounding neurons in the spinal cord's dorsal horn [49]. Additionally, the reduction of K ir4.1 expression in SGCs has been reported in different pain models [11,24,25,50].…”
Section: Discussionmentioning
confidence: 99%
“…A similar effect was reported in hyperglycaemic cultured astrocytes and in mouse models of diabetes. Hyperglycaemia downregulates K ir4.1 protein in vitro and in vivo, resulting in the increased spontaneous activity of surrounding neurons in the spinal cord's dorsal horn [49]. Additionally, the reduction of K ir4.1 expression in SGCs has been reported in different pain models [11,24,25,50].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in diabetic mice, whole‐cell patch‐clamp recordings in hippocampal brain slices showed decreased Kir4.1 currents, resulting in impaired potassium homeostasis and increased excitability (Méndez‐González et al., 2020). Metformin, a widely used antidiabetic drug, was observed to increase Kir4.1 expression (Alex et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Méndez‐González et al. (2020) revealed that hyperglycemia could downregulate Kir4.1 in cultured astrocytes, which could be demonstrated by depolarized membrane potential, reduced barium‐sensitive Kir currents and impaired potassium uptake capabilities of hippocampal astrocytes (Méndez‐González et al., 2020). Sun et al.…”
Section: Genetic Dysfunction Of Potassium Channels and Asd: From Genotypes To Phenotypesmentioning
confidence: 99%